What Is Effective Aid? How Would Donors Allocate It? - Kenny, Charles (World Bank, Washington, DC, 2012)
There are significant weaknesses in some of the traditional justifications for assuming that aid will foster development. This paper looks at what the cross-country aid effectiveness literature and World Bank Operations Evaluation Department reviews have suggested about effective aid, first in terms of promoting income growth, and then for promoting other goals. This review forms the basis for a discussion of recommendations to improve aid effectiveness and a discussion of effective aid allocation. Given the multiple potential objectives for aid, there is no one right answer. However, it appears that there are a number of reforms to aid practices and distribution that might help to deliver a more significant return to aid resources. We should provide aid where institutions are already strong, where they can be strengthened with the help of donor resources, or where they can be bypassed with limited damage to existing institutional capacity. The importance of institutions to aid outcomes, as well as the fungibility of aid flows, suggests that programmatic aid should be expanded in countries with strong institutions, while project aid should be supported based on its ability to transfer knowledge and test new practices and support global public good provision rather than (merely) as a tool of financial resource transfer. The importance of institutions also suggests that we should be cautious in our expectations regarding the results of increased aid flows.